Interpretation of Transbronchial Lung Biopsies from Lung Transplant Recipients:Inter- and Intraobserver Agreement. Issue 2 (3rd May 2005) - Stephenson, Anne; Flint, Julia; English, John; Vedal, Sverre; Fradet, Guy; Chittock, Dean; Levy, Robert D
Abstract : BACKGROUND: Transbronchial lung biopsy results are crucial for the management of lung transplant recipients. Little information is available regarding the reliability and reproducibility of the interpretation of transbronchial lung biopsies. OBJECTIVE: To examine the inter-reader variability between two lung pathologists with expertise in lung transplantation. METHODS: Fifty-nine transbronchial lung biopsy specimens were randomly selected. Active infection had been excluded in all cases. The original interpretations (as per the Lung Rejection Study Group) for acute rejection grade included 19 biopsies scored as A0 (none), 14 scored as A1 (minimal), 12 as A2 (mild), 11 as A3 (moderate) and three as A4 (severe). The pathologists worked independently without clinical information or knowledge of the original interpretation. The specimens were graded using the Lung Rejection Study Group criteria for acute rejection (grades A0 to A4), airway inflammation (grades B0 to B4) and bronchiolitis obliterans (C0 absent and C1 present). Between-reader agreement for each category was analyzed using a Kappa statistic. RESULTS: Because many transplant specialists initiate augmented immunosuppression with biopsy grades of A2 or higher, results for each reader were dichotomized as A0/A1 versus A2/A3/A4. Using this dichotomy, there was only moderate agreement (kappa 0.470, P<0.001) between readers. For categories B and C, the results were dichotomized for the absence or presence of airway inflammation and bronchiolitis obliterans, respectively. The level of agreement between readers was fair for category B (kappa 0.333, P=0.014) and poor for category C (kappa 0.166, P=0.108). The intrareader agreement for acute rejection was substantial (kappa 0.795, P=0.0001; kappa 0.676, P=0.0001). CONCLUSIONS: Because the agreement between expert pathologists is only modest, optimum clinical decision-making requires that transbronchial lung biopsy results be used in an integrated clinical context.